(3GdYhdeI hGdJfejI GdHTQjI GdeSJOGeI aj GdhWf GdYQHjs - (3QYO SGej YHO GdQRGb(B, (3GdJejejs ((3YeGf(B:s (3OGQ OLdI(B,s, 2008)
(3GdeMJhjGJ (B: (3GdebOeI(B-(3GdaUd GdChd (B: (3GdYhdeI hGdJfejI GdHTQjI GdeSJOGeI (B: (3GdYhdeI hGdJfejI GdHTQjI (B: (3eaghe GdYhdeI (B: (3Gdeaghe GdGbJUGOi ddYhdeI (B: (3GdYhdeI hGdGeQcI (B: (3GdLPhQ GdJCQjNjI ddYhdeI (B: (3JWhQ GdJfejI GdHTQjI (B: (3GdJfejI GdHTQjI ai GdNeSjfjGJ (B: (3GdJfejI GdHTQjI ai GdSJjfjGJ (B: (3GdJfejI GdHTQjI GdeSJOGeI (B: (3eaghe GdJfejI GdHTQjI GdeSJOGeI (B: (3ebGjjS GdJfejI GdHTQjI GdeSJOGeI (B: (3Odjd GdJfejI GdHTQjI (B(HDI) : (3GdJfejI GdGfSGfjI hebGjjSgG (B: (3GdJfejI GdGfSGfjI (B: (3ebGjjS JbQjQ GdJfejI GdGfSGfjI GdYQHjI(B-(3GdaUd GdKGfi (B: (3hGbY GdJfejI GdHTQjI ai GdhWf GdYQHi (B: (3GdhGbY GdSjGSi hGdYScQi (B: (3GfXeI GdMce hbVjI GdOjehbQGWjI (B: (3GdOSGJjQ GdYQHjI hbVGjG Mbhb GdGfSGf (B: (3GdUQGY hGdfRGYGJ GdYScQjI (B: (3GdUQGY GdYQHi(B-(3GdESQGFjdi (B: (3GdhGbY GdGLJeGYi (B: (3GdhGbY GdJYdjei (B: (3GdhGbY GdHjFi(B-(3GdaUd GdKGdK (B: (3EfYcGSGJ GdYhdeI Ydi GdJfejI GdHTQjI GdeSJOGeI ai GdhWf GdYQHi (B: (3GdGfYcGSGJ GdSjGSjI hGdYScQjI (B: (3GdOjehbQGWjI hGdJYOOjI GdSjGSjI (B: (3GdMce GdUGdM (B: (3YGdejI Mbhb GdGfSGf (B: (3GdGQgGH GdOhdi (B: (3GdGfYcGSGJ GdGLJeGYjI (B: (3GdGfYcGSGJ GdGbJUGOjI (B: (3GdTQcGJ eJYOOI GdLfSjI (B: (3UfOhb GdfbO hGdHfc GdOhdjjf (B: (3efXeI GdJLGQI GdYGdejI (B: (3YhdeI GdJLGQI (B: (3GdJLGQI GdYQHjI GdHjfjI (B: (3GdJLGQI GdGdcJQhfjI(B.s
(3HjHdjhZQGajG U(B.260-284s
Keywords: (3GbJUGO GdOhdjs; (3HdOGf YQHjIs; (3YhdeIs